2017
DOI: 10.4102/sajems.v20i1.1498
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the value relevance of interim and annual financial statements

Abstract: Background: This study tests the value relevance of interim accounting information. The study also explores whether the value relevance of annual and interim financial statements has changed over time.Aim: It explores whether the value relevance of interim financial statements is higher than the value relevance of annual financial statements. Finally, it investigates whether accounting information published in interim and annual financial statements has incremental value relevance.Setting: Data for the period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
1
7
1
Order By: Relevance
“…In Malaysia, Mirza, Malik and Abdul-Hamid (2018) concluded that book value (BV) has value relevance whilst earnings do not have any usefulness in explaining share prices. This conforms with conclusions by Zulu, De Klerk and Oberholster (2017) who studied usefulness of interim financial statements by using a data set of JSE-listed firms.…”
Section: Related Literaturesupporting
confidence: 90%
See 1 more Smart Citation
“…In Malaysia, Mirza, Malik and Abdul-Hamid (2018) concluded that book value (BV) has value relevance whilst earnings do not have any usefulness in explaining share prices. This conforms with conclusions by Zulu, De Klerk and Oberholster (2017) who studied usefulness of interim financial statements by using a data set of JSE-listed firms.…”
Section: Related Literaturesupporting
confidence: 90%
“…On the contrary, evidence from the same market (JSE) provided by Sixpence and Adeyeye (2019) shows that operating income has value relevance, whilst BV is not relevant, based on a dynamic panel of JSE-listed firms. However, these two studies used different variables; Zulu et al (2017) used market capitalisation as the response variable, whilst Sixpence and Adeyeye (2019) used share prices. Furthermore, the earnings measure used is different; whilst Sixpence and Adeyeye (2019) used operating income, Zulu et al (2017) used net profit after tax.…”
Section: Related Literaturementioning
confidence: 99%
“…A section of literature documents that negative earnings barely have an association with share price movements (Joos & Plesko, 2005;Darrough & Ye, 2007;Venter et al, 2014;Zulu et al, 2017). Zulu et al (2017) tested the value relevance of losses and found that negative earnings affect value relevance of financial statements on the Johannesburg Stock Exchange (JSE). Further evidence to this was provided by Collins et al (1997), Filip and Raffournier (2010) as well as Venter et al (2014).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…This is not a guarantee of value relevance of financial statement information, but it certainly increases that probability as compared to the shunned loss-makers. This, coupled with previous research (Collins, Maydew, & Weiss, 1997;Filip & Raffournier, 2010;Venter, Emanuel, & Cahan, 2014;Zulu, De Klerk, & Oberholster, 2017), motivated the researchers to investigate the impact of profit or loss on value relevance of EBIT and book value on the Zimbabwe Stock Exchange (ZSE). The ZSE was chosen because it is one of the alternatives to equity investors in Southern Africa who would want to diversify their equity portfolios across territorial boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…A recent comparison of indicators from interim and annual financial statements against the background of verification of the Ohlson model was performed focusing on the RSA market [29]. In spite of the fact that these indicators comprise only the basic parameters offered by Ohlson, it should be noted that the relevant specifications indirectly measure the level of investors' confidence in the audited annual reports.…”
Section: Literature Reviewmentioning
confidence: 99%